The Effect Of Return On Assets, Return On Equity, Debt On Equity Ratio, And Company Size On Firm Value In Manufacturing Companies Listed On The Indonesian Stock Exchange - Pianus Giawa; Febry Afifah Irwan; Bayu Wulandari; Muhammad Habibie (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to analyze the effect of return on asset (ROA), return on equity (ROE), debt-to-equity ratio (DER), and company size on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018–2022. Multiple linear regression with panel data serves as the research method. The research sample consists of manufacturing companies listed on the IDX during that period. The results showed that ROA and ROE have a significant positive effect on firm value. This indicates that the company's profitability, as measured by return on assets and equity, is an important factor in increasing firm value. In contrast, DER and firm size do not have a significant influence on firm value. These data indicate that in Indonesia's manufacturing industry, company value is not primarily influenced by capital structure and firm size. The study suggests that manufacturing company management should prioritize enhancing operational efficiency and profitability to enhance firm value. When conducting company evaluations, investors can also consider profitability measures such as Return on Assets (ROA) and Return on Equity (ROE). Regulators and politicians should promote transparency and accountability while also fostering innovation in the manufacturing sector. Additional research is necessary to explore additional variables that may influence the value of a company.